A new series of Co, Ni, Zn, and Cd metal–organic architectures driven by an unsymmetrical biphenyl-tricarboxylic acid: hydrothermal assembly, structural features and properties. Issue 22 (18th May 2018) - Gu, Jin-Zhong; Cai, Yan; Qian, Zi-Yue; Wen, Min; Shi, Zi-Fa; Lv, Dong-Yu; Kirillov, Alexander M.
Abstract : Twelve new Zn(ii ), Ni(ii ), Co(ii ), and Cd(ii ) coordination compounds with diverse dimensionalities were assembled using 3′-nitro-biphenyl-2, 4, 4′-tricarboxylic acid as a main building block. Abstract : This study reports the hydrothermal synthesis of a novel series of twelve coordination compounds, namely, [Cd(μ-Hnbtc)(H2 O)4 ]·H2 O n (1 ), [Zn2 (μ-Hnbtc)2 (phen)2 ]·2H2 O (2 ), [Zn(Hnbtc)(phen)2 (H2 O)]·4.5H2 O (3 ), [Ni(Hnbtc)(phen)2 (H2 O)]·6H2 O (4 ), [Zn2 (μ-Hnbtc)2 (2, 2′-bipy)2 ]·2H2 O (5 ), [Cd3 (μ5 -nbtc)(μ6 -nbtc)(2, 2′-bipy)2 (H2 O)] n (6 ), [Zn3 (μ3 -nbtc)2 (phen)3 (H2 O)2 ]·4H2 O (7 ), [Co(H2 O)6 ][Co2 (nbtc)2 (μ-4, 4′-bipy)(4, 4′-bipy)2 (H2 O)6 ]·8H2 O (8 ), [Ni3 (μ4 -nbtc)2 (μ-4, 4′-bipy)2.5 (μ-H2 O)(H2 O)3 ]·4H2 O n (9 ), [Cd2 (μ4 -nbtc)(μ-OH)(2, 2′-bipy)2 ]·H2 O n (10 ), [Cd2 (μ4 -nbtc)(μ-OH)(phen)2 (H2 O)] n (11 ), and [Zn2 (μ5 -nbtc)(μ3 -OH)(μ-4, 4′-bipy)]·4, 4′-bipy·H2 O n (12 ), which are derived from 3′-nitro-biphenyl-2, 4, 4′-tricarboxylic acid (H3 nbtc) as a virtually unexplored building block. These compounds were generated in aqueous medium from the corresponding metal(ii ) chlorides as a metal source, H3 nbtc as a principal building block, NaOH as a base, and simple N, N-donor aromatic ligands as crystallization mediators ( i.e., 1, 10-phenanthroline, phen; 2, 2′-bipyridine, 2, 2′-bipy; or 4, 4′-bipyridine, 4, 4′-bipy). All products1–12 were completely characterized in the solid state by IR spectroscopy, elemental and thermogravimetric (TGA) analyses, powder (PXRD) and single-crystal X-ray diffraction. Structures of1–12 range from discrete 0D dimers (2 and5 ) or monomers (3, 4, and8 ) to 1D coordination polymers (CPs, 1, 6, 7, 10, and11 ) and 3D metal–organic frameworks (MOFs, 9 and12 ). A broad structural diversity of1–12 is guided by the type of the metal(ii ) node, the molar ratio between H3 nbtc and sodium hydroxide, and the kind of crystallization mediator. Topological analysis and classification of metal–organic underlying nets was made, disclosing the following topological types:2C1 (in1 and7 ), 1M2-1 (in2 and5 ), SP1 -periodic net (in10 and11 ), tfz-d (in12 ), and some topologically unique nets (in6 and9 ). Luminescence behavior of1–3, 5–7, and10–12 was studied in the solid state. Magnetic properties of a Ni(ii ) MOF9 were also investigated and modeled. All obtained products1–12 represent the first structurally characterized examples of coordination compounds derived from H3 nbtc, thus opening up its application in coordination chemistry as a novel tricarboxylate building block.